A multidomain approach to asteroid families' identification - Carruba, V. [UNESP]; Domingos, R. C.; Nesvorny, D.; Roig, F.; Huaman, M. E. [UNESP]; Souami, D. (Oxford University Press, 2013)
It has been shown that large families are not limited to what found by hierarchical clustering methods in the domain of proper elements (a, e, sin(i)), which seems to be biased to find compact, relatively young clusters, but that there exists an extended population of objects with similar taxonomy and geometric albedo, which can extend to much larger regions in proper elements and frequencies domains: the family 'halo'. Numerical simulations can be used to provide estimates of the age of the family halo, which can then be compared with ages of the family obtained with other methods. Determining a good estimate of the possible orbital extension of a family halo is therefore quite important, if one is interested in determining its age and, possibly, the original ejection velocity field. Previous works have identified families' haloes by an analysis in proper elements domains, or by using Sloan Digital Sky Survey-Moving Object Catalog data, fourth release (SDSS-MOC4) multiband photometry to infer the asteroid taxonomy, or by a combination of the two methods. The limited number of asteroids for which geometric albedo was known until recently discouraged in the past the extensive use of this additional parameter, which is however of great importance in identifying an asteroid taxonomy. The new availability of geometric albedo data from the Wide-field Infrared Survey Explorer (WISE) mission for about 100 000 asteroids significantly increased the sample of objects for which such information, with some errors, is now known. In this work, we proposed a new method to identify families' haloes in a multidomain space composed by proper elements, SDSS-MOC4 (a*, i - z) colours, and WISE geometric albedo for the whole main belt (and the Hungaria and Cybele orbital regions). Assuming that most families were created by the breakup of an undifferentiated parent body, they are expected to be homogeneous in colours and albedo. The new method is quite effective in determining objects belonging to a family halo, with low percentages of likely interlopers, and results that are quite consistent in term of taxonomy and geometric albedo of the halo members.
Keywords: Celestial mechanics; minor planets; asteroids: general